The energy balance hypothesis of obesity: do the laws of thermodynamics explain excessive adiposity? - Torres Carot, Vicente; Suárez González, Andrés; Lobato Foulques, Cecilia (My University, 2022)
In this work, we reflect upon the energy balance hypothesis of obesity. International organizations, the general population and many scientists hold the belief that obesity is indisputably caused by an imbalance between energy intake and energy expenditure. Most of them argue that the laws of thermodynamics support this view. We identify and review the main arguments used to support this belief, and we explain the reasoning mistakes those arguments harbor. We show that the laws of thermodynamics do not support the idea that obesity is an energy problem nor an energy balance problem more than they do in the growth of any other tissue in the human body. We argue that the validity of the energy balance paradigm for obesity must be questioned. Although correction of a wrong belief is laudable per se, in this particular case harm may arise by influencing the way in which obesity prevention is tackled and obese patients are treated.